THE DEVELOPMENT OF PORTABLE AIR QUALITY DETECTION (Journal of Technology and Operations Management, 2020)
Air quality is very important to ensure the health of humans, plants, and even animals. The tragedy of chemical waste disposal in the Kim Kim river has resulted in air pollution in the surrounding area. Therefore, this innovation has been developed to produce a mobile device that has a low cost, detection of the gas in real-time, and overcome the problems faced due to chemical waste pollution such as shortness of breath, nausea, and vomiting. Portable air quality detection is an innovation used to detected and measured the connections between software and hardware that are required for analysis purposes. The outputs detected are carbon dioxide, benzene, alcohol, ammonia, nitrogen oxide, and smoke. Data analysis was done by making a comparison between the output values in LCD and Favoriot and Blynk. This project also can measure the value of temperature and humidity. The sensor used to detect gas readings is MQ135 gas sensor and for temperature and humidity sensor is DHT22 sensor. The value of gas, temperature, and humidity in the environment will be displayed on the website as well as on the phone applications. This innovation used two types of platforms to display the data, Favoriot in website platform and Blynk used on smartphones. In addition, this value will be recorded and stored on the website for future use by the users. The users will also be able to compare readings before and after to ensure that the air in the environment is in good condition. In addition, this project can warn users if the reading is at danger level. The buzzer will sound and users will be notified by email. For future recommendations, the A3OZ sensor can be used to achieve high precision values for O3 and NO2 readings with a detection range of 0-10 ppm and detection accuracy of 20 ppb